2010
DOI: 10.1097/jto.0b013e3181f1c7b0
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib in Advanced Non-small Cell Lung Cancer: Efficacy and Safety Findings of the Global Phase IV Tarceva Lung Cancer Survival Treatment Study

Abstract: These data confirm the favorable efficacy and safety profile of erlotinib in a large heterogeneous non-small cell lung cancer population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
86
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 20 publications
14
86
3
1
Order By: Relevance
“…The cut-off date for the final analysis was 17 April, 2009. The findings of the study confirmed the favourable efficacy and safety profile of erlotinib in a large heterogeneous population of NSCLC patients; the 1-year survival rate was 37.7%, and median OS and progressionfree survival (PFS) were 7.9 and 3.25 months, respectively (14). The large size of the study database made it feasible to evaluate outcomes among the large number of older patients (≥70 years) who participated; this report describes outcomes among elderly patients who received erlotinib as their first line therapy.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…The cut-off date for the final analysis was 17 April, 2009. The findings of the study confirmed the favourable efficacy and safety profile of erlotinib in a large heterogeneous population of NSCLC patients; the 1-year survival rate was 37.7%, and median OS and progressionfree survival (PFS) were 7.9 and 3.25 months, respectively (14). The large size of the study database made it feasible to evaluate outcomes among the large number of older patients (≥70 years) who participated; this report describes outcomes among elderly patients who received erlotinib as their first line therapy.…”
Section: Introductionsupporting
confidence: 60%
“…TRUST first-line TRUST AEs, n (%) elderly population overall population (14) Patients with at least one treatment-related AE Other than the pre-specified events defined in the protocol. AE, adverse event; SAE, serious adverse event; TRUST, TaRceva LUng cancer Survival Treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few agents including docetaxel, pemetrexed, gefitinib and erlotinib have shown to be effective in the second-line and third-line chemotherapy for advanced NSCLC (Shepherd et al, 2005;Thatcher et al, 2005;Barlesi et al, 2006;Cullen et al, 2008;Kim et al, 2008;Scagliotti et al, 2009;Cappuzzo et al, 2010;Douillard et al, 2010;Reck et al, 2010;Vamvakas et al, 2010). Despite an increasing proportion of patients with advanced NSCLC derive prolonged survival with novel chemotherapy regimens; many of them will require salvage chemotherapy after relapse (Kosmas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Anilinoquinazolines are the most developed class of drugs that inhibit EGFR tyrosine kinase intracellularly 10,11 . Anilinoquinazoline-containing compounds, erlotinib (Tarceva Õ ) 12,13 and gefitinib (Iressa Õ ) 14 have been approved for chemotherapeutic treatment of patients with advanced non-small cell lung cancer. Our strategy is directed toward designing ligands which are structurally similar to the basic skeleton, 4-anilinoquinazoline of erlotinib through replacing quinazoline ring with benzothiazole since both are isosteric with adenine portion of ATP and can mimic the ATP competitive binding regions of EGFR tyrosine kinase.…”
Section: Introductionmentioning
confidence: 99%